Diagnostic Accuracy of Pelvic MRI and Transvaginal Ultrasound for Detecting Uterine Fibroids and Adenomyosis. A Cross-Sectional Comparative Study - Shazia Ashraf, Aisha Asim, Aisha Taj, Yasma Ashraf, Rajesh Kumar, Sadia Asghar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Uterine fibroids and adenomyosis are common gynecological conditions responsible for abnormal uterine bleeding, dysmenorrhea, pelvic pain, and infertility. Early and accurate diagnosis is essential for guiding appropriate management. Transvaginal ultrasound (TVUS) is widely used as the first-line imaging tool, while pelvic magnetic resonance imaging (MRI) is considered the gold standard. This study compared the diagnostic accuracy of TVUS and MRI in detecting uterine fibroids and adenomyosis, using histopathology as the reference standard. Methods: A cross-sectional comparative study was conducted at the General Teaching Hospital (GMC/GTH), Gujranwala, and Liaquat National Hospital, Karachi, from January 2022 to June 2023. A total of 90 women aged 25–50 years presenting with abnormal uterine bleeding, dysmenorrhea, pelvic pain, or infertility were included. All participants underwent TVUS followed by pelvic MRI. Subsequent hysterectomy or myomectomy provided specimens for histopathological confirmation. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated. Results: Histopathology confirmed fibroids in 58 cases (64.4%), adenomyosis in 24 cases (26.7%), and combined pathology in 8 cases (8.9%). For fibroids, TVUS achieved a sensitivity of 83% and specificity of 75%, while MRI demonstrated a sensitivity of 95% and specificity of 90%. For adenomyosis, TVUS showed a sensitivity of 70% and specificity of 68%, compared to MRI with sensitivity of 90% and specificity of 85%. MRI consistently provided higher diagnostic accuracy and better differentiation of coexisting lesions. Conclusion: TVUS remains a practical first-line imaging modality due to cost-effectiveness and accessibility. However, MRI offers superior diagnostic accuracy and should be reserved for complex, inconclusive, or preoperative cases to optimize patient management. Keywords: Uterine fibroids, Adenomyosis, Transvaginal ultrasound, Pelvic MRI, Diagnostic accuracy